2015
DOI: 10.4028/www.scientific.net/ssp.233-234.233
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Electrical and Magnetic Properties of Ni<sub>47-x</sub>Mn<sub>42+x</sub>In<sub>11</sub> (x=0, 1, 2) Based Heusler Alloys

Abstract: Magnetic, magnetocaloric and transport properties of alloys of system Ni-Mn-In has been investigated. Large magnetocaloric effect have been observed at temperatures below room, making it a potential material system for various applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…2. For all samples at temperatures below room temperature, features are observed that probably indicate a structural phase transition of the first order, accompanied by hysteresis inherent in similar alloys of nonstoichiometric composition Ni-Mn-X (X = Ga, In, Sn, Sb) [3][4][5].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…2. For all samples at temperatures below room temperature, features are observed that probably indicate a structural phase transition of the first order, accompanied by hysteresis inherent in similar alloys of nonstoichiometric composition Ni-Mn-X (X = Ga, In, Sn, Sb) [3][4][5].…”
Section: Resultsmentioning
confidence: 93%
“…It is known [1,2] that FM Heusler alloys based on Ni-Mn undergo the first-order phase transition between the low-temperature martensitic phase and the high-temperature austenite phase, which is accompanied by the sharp change in magnetization and electrical resistance. In Ni 47−x Mn 42+x In 11 (x = 0, 1, 2) alloys, this transition and large MCE values are observed in the room temperature region, [3]. This makes these alloys promising for use as a refrigerant.…”
Section: Research Of "mentioning
confidence: 90%
“…2. Для всех образцов при температурах ниже комнатной наблюдаются особенности, вероятно указывающие на структурный фазовый переход первого рода сопровождающийся гистерезисом, свойственным подобным сплавам нестехиометрического состава Ni-Mn-X (X = Ga, In, Sn, Sb) [3,4,5].…”
Section: результаты и обсуждениеunclassified
“…Известно [1,2], что ФМ-сплавы Гейслера на основе Ni−Mn претерпевают фазовый переход первого рода между низкотемпературной мартенситной фазой и высокотемпературной аустенитной, который сопровождается резким изменением намагниченности и электросопротивления. В сплавах Ni 47−x Mn 42+x In 11 (x = 0, 1, 2) данный переход и большие значения МКЭ наблюдаются в районе комнатной температуры [3]. Это делает данные сплавы перспективными для применения в качестве хладагента.…”
Section: Introductionunclassified
“…В работах [4,8] нами было показано существенное влияние внешнего магнитного поля на смещение температуры мартенситного превращения в сплавах Ni−Mn−In при замещении атомов никеля атомами марганца. Были исследованы магнитные и транспортные свойства этой системы сплавов [9]. В литературе приводятся только отдельные работы, касающиеся термоциклической обработки сплавов, например, таких…”
unclassified